Using Adomian decomposition method for solving a vector-host model - Elmojtaba, Ibrahim (International Journal of Applied Mathematical Research, 2016)
In this paper, we use Adomian decomposition method (ADM) for solving a vector-host model by using an alternate algorithm suggested by Biazar et. al [4]. Some of the first terms were generated and plotted against time and compared our results with the regular Runge-Kutta numerical methods by using Matlab ode45 function.